2015
DOI: 10.18006/2015.3(5).430.439
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of soybean [Glycine max (L.) Merrill] production system in Benin

Abstract: Present study was conducted to analyze the soybean production system in Benin. Data were collected from 324 soybean producers selected from the three major soybean-producing agro-ecological areas i.e. agro-ecological zone 3 (southern Borgou), agro-ecological zone 4 (West Atacora) and agro-ecological zone 5 (Cotton zone of the Centre of Benin). A participatory research approach with group discussions followed by individual interviews was carried out for extracting the information from respondents. Information m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Men also have more access to information in the study area than women, which allows them to look for ways to boost productivity. This is consistent with the findings of Zoundji et al (2015) which concluded that, soybean cultivation is dominated by males. Saïdou et al (2007) argued that males are normally landowners; they also inherit land from their parents much more than their female counterparts.…”
Section: Determinants Of Cf Among Soybean Producerssupporting
confidence: 93%
“…Men also have more access to information in the study area than women, which allows them to look for ways to boost productivity. This is consistent with the findings of Zoundji et al (2015) which concluded that, soybean cultivation is dominated by males. Saïdou et al (2007) argued that males are normally landowners; they also inherit land from their parents much more than their female counterparts.…”
Section: Determinants Of Cf Among Soybean Producerssupporting
confidence: 93%
“…These results mean that education level has a negative impact on the efficiency of the soybean seed breeder farming. The findings of this study show a negative relationship between education levels to increasing efficiency which are in line with the findings of Zoundji et al (2015) who also found the impact of education levels are negatively related to soybean farming efficiency. Based on this finding, it can be seen that education level in soybean farming does not play a significant role in determining the technical procurement of farming well.…”
Section: Efficiency Determinants Of Soybean Seed Breeding Businesssupporting
confidence: 91%
“…In addition, Riska (2014) surveyed 30 respondents to analyze the production and profit of A. hypogaea farm. Zoundji et al (2015) selected 324 soybean producers as respondents.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, Zoundji et al (2015) found that 60.5%, 28.1%, and 11.4% of the soybean farmers in Benin had low (< 700 kg ha -1 ), medium (between 700 and 1,000 kg ha -1 ), and high (> 1,000 kg ha -1 ) yield level, respectively (Table 6). The soybean grain yields obtained after harvest are inferior to 1,000 kg ha -1 for the majority of respondents.…”
Section: A B C Dmentioning
confidence: 99%
See 1 more Smart Citation